2015
DOI: 10.1016/j.ejrad.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Using quantitative image analysis to classify axillary lymph nodes on breast MRI: A new application for the Z 0011 Era

Abstract: Purpose To assess the performance of computer extracted feature analysis of dynamic contrast enhanced (DCE) magnetic resonance images (MRI) of axillary lymph nodes. To determine which quantitative features best predict nodal metastasis. Methods This institutional board-approved HIPAA compliant study, in which informed patient consent was waived, collected enhanced T1 images of the axilla from patients with breast cancer. Lesion segmentation and feature analysis were performed on 192 nodes using a laboratory-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Baltzer et al [ 27 ] investigated only the margin of lymph nodes as a morphological parameter reporting a sensitivity of 41.2% and a specificity of 95.2%. Schacht et al [ 28 ] reported the results of a quantitative breast MR image analysis for classification of axillary lymph nodes. The best features in that study were the circularity as a morphological parameter with AUROC of 0.67 and the wash-out rate with AUROC of 0.62.…”
Section: Discussionmentioning
confidence: 99%
“…Baltzer et al [ 27 ] investigated only the margin of lymph nodes as a morphological parameter reporting a sensitivity of 41.2% and a specificity of 95.2%. Schacht et al [ 28 ] reported the results of a quantitative breast MR image analysis for classification of axillary lymph nodes. The best features in that study were the circularity as a morphological parameter with AUROC of 0.67 and the wash-out rate with AUROC of 0.62.…”
Section: Discussionmentioning
confidence: 99%
“…Since breast MRI is considered a very useful imaging modality in assessing breast tumor response to neoadjuvant chemotherapy (9, 10), developing and applying breast MRI image feature analysis based on the quantitative image feature analysis or CAD schemes to assess complete response of the breast tumors to the neoadjuvant chemotherapy has been attracting research interest (20, 21). In this paper we reported our latest progress to develop and test new quantitative image feature analysis schemes to assess breast tumor response to the neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques include contrast-enhanced T1w MRI methods, as well as T2w sequences and DWI. 22,31 LN staging is usually based on size of LNs, relative T 2 values, morphology, For the T1-FFE, T2-VISTA and T2-FFE examples, maximum intensity projections of three slices were used to increase signal-to-noise ratio and to cover the same volume as in the T2-TSE and DWI.…”
Section: Discussionmentioning
confidence: 99%